Balancing Heritage in Urban Expansion: Gedung Sate’s Resilience towards a JunkSpace Landscape - Hanindasaputra, Sebastian Emillio; Sunaryo, Rony Gunawan; Redyantanu, Bramasta Putra (Petra Christian University, 2026)
This paper argues that the vertical stratification of formal, informal, and historical layers in Bandung contributes to the emergence of Junkspace, particularly around Gedung Sate, a heritage government building embedded in a rapidly urbanizing context. Drawing on Koolhaas’ concept of Junkspace and theories of spatial heterogeneity, the research explores how informal peripheries intersect with formal urban growth, creating porous hybrid spaces that defy conventional spatial order. Through qualitative spatial analysis, street-level observations, and time-lapse figure-ground studies from 2017 to 2025, the study reveals that informal structures adapt to, rather than displace, formal ones. This coexistence generates architectural incoherence marked by non-hierarchical, fused uses. The findings suggest that Gedung Sate is evolving into a form of Junkspace not merely through the erosion of spatial order but through active transformations that blend historical permanence with dynamic informal encroachments, reflecting the complex and layered realities of contemporary Bandung.